MEASURES THAT MATTER: AN EMPIRICAL INVESTIGATION OF INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE IN CONVENTIONAL BANKING COMPANIES - Marpaung, Aldio; Muharam, Harjum (Penerbit Lafadz Jaya, 2024)
This study aims to determine the influence of intellectual capital of the conventional banking industry in Indonesia on financial performance for the 2020 - 2023 period. This study analyzes the performance of intellectual capital using the A-VAIC method which has three indicators, namely Human Capital Efficiency (HCE), Innovation Capital Efficiency (INVCE), and Capital Employed Efficiency (CEE) as independent variables. Financial performance in this study was measured using Return On Asset (ROA) as a dependent variable. This study is a descriptive quantitative research, with secondary data sources obtained from the annual financial statements of the conventional banking industry listed on the Indonesia Stock Exchange and accessible through www.idx.co.id. This study examined the influence of banking intellectual capital for 4 years with a sample of 64 financial statement data. Data analysis uses multiple regression analysis with the help of Eviews software. The results of the analysis showed that HCE had a positive and significant effect on ROA, and INVCE had a negative and significant effect on ROA, while CEE had no effect on ROA.